L4 fixation is not necessary in L5-Iliac spinopelvic fixation after trauma, but coadjutant transilio-transsacral fixation is - Sevillano-Pérez, Enrique; Prado-Novoa, María; Postigo-Pozo, Sergio; Peña Trabalón, Alejandro; Guerado-Parra, Enrique (Elsevier, 2024)
Spinopelvic dissociation (SPD) is a severe injury characterized by a discontinuity between the spine and the bony pelvis consisting of a bilateral longitudinal sacral fracture, most of the times through sacral neuroforamen, and a horizontal fracture, usually through the S1 or S2 body.. Since SPD results after high energy injuries, like a fall from height, traffic accidents or blast injuries , most of the times it is found in a polytraumatized patient, associated with other life-threatening injuries Conservative treatment is chosen only in patients who are not fit for surgery or have concomitant injuries that will require a period of immobilization longer than three months and in those presenting mild displacement at the fracture sites]. Otherwise, SPD lesions are best treated by surgical procedures.
Keywords: Huesos pélvicos; Traumatología; Cirugía; Columna vertebral - Cirugía; Spinopelvic dissociation; Lumbopelvic dissociation; Sacral fractures; Fractures of the sacrum; Iliosacral screw; Transiliac-transsacral screw; Spinopelvic fixation; Spinopelvic stabilization; Pelvic fixation; Triangular osteosynthesis